Surface topology modification of organic substrates using material jetting technologies. (November 2020) - Chen, Tiffany; Dilag, Jessirie; Bateman, Stuart
Abstract: The ability to directly modify the topology of a surface with three-dimensional micron-scale features provides both a mechanism of controlling how it interacts with the surrounding environment and the potential to impart functional features. Using direct material jetting based additive manufacturing technologies, we report the direct printing of microstructures onto aluminium coupons previously finished with polyurethane (PU) coatings where the overcoat window proved crucial for this process. The effect of PU coating's age on the development of strong interfacial interactions and hence the level of adhesion achieved between the photopolymer and the topcoat was explored. With aging, the PU coatings were shown to increase in cross-link density which resulted in reduced levels of adhesion with the photopolymer observed. This was reflected in changes in surface energy hence surface chemistry via XPS analysis. Changes in the interfacial interactions were qualitatively examined through SEM analysis of the photopolymer – PU coating interface which showed localized debonding (de-wetting) of the photopolymer when printing was performed on aged PU topcoats. Graphical abstract: Unlabelled Image Highlights: Techniques to print microstructures onto PU coatings using material jetting based additive manufacturing were demonstrated PU coating age was shown to influence the level of adhesion achieved between the photopolymer and coating. On aging PU coatings were demonstrated to change in cross-link density and surface chemistry Photopolymer printed onto aged PU coatings showed regions of de-bonding and poor surface wetting.